(untitled) (CIPEEX, 2025)
THE GRANTING OF MATERNITY LEAVE FOR NON-GESTATIONAL MOTHERS IN SAME-SEX COUPLESThis study examines the provision of maternity leave for non-gestational mothers in same-sex relationships, focusing on the investigation of the legal foundations for such a benefit. The central objective is to assess whether current legislation can be interpreted to include the protection of motherhood across all forms of family structures. To this end, the research employs the method of sociological interpretation, analyzing existing legislation and relevant judicial rulings. The methodology involves a detailed analysis of legal norms and judicial decisions, aiming to identify how the legislation can be applied or adapted to encompass the protection of motherhood in non-traditional family contexts. Through this approach, the study seeks to determine whether current legislation supports an interpretation that guarantees the rights of all mothers, regardless of their biological configuration or sexual orientation. The findings indicate the feasibility of developing a normative framework that aligns with jurisprudence and the constitutional values of equality and non-discrimination. Furthermore, the research underscores the importance of recognizing family bonds and motherhood as essential elements, irrespective of the biological constitution of families. In doing so, it is possible to promote more inclusive legislation that reflects the diversity of contemporary family relationships and ensures the rights of all mothers, thereby strengthening the principles of justice and equality.